Local Tumor Behavior Associated With Survival Among Patients With Paraganglioma of the Head and Neck. Issue 1 (March 2022) - Harley, Randall J.; Lee, Jason H.; Ostrander, Benjamin T.; Finegersh, Andrey; Pham, Tammy B.; Tawfik, Kareem O.; Ren, Yin; Faraji, Farhoud; Friedman, Rick A.
Objective: The purpose of this study was to evaluate the utility of ICD-O-3 –classified local tumor behavior as a prognosticator of head and neck paraganglioma (HNP) outcomes. Study Design: Retrospective cohort study. Setting: National Cancer Database between 2004 and 2016. Methods: This study included patients aged ≥18 years who were diagnosed with HNP. Clinical outcomes and clinicopathologic features were compared with regard to local tumor behavior. Results: Our study included 525 patients, of which the majority had HNP classified as locally invasive (45.9%) or borderline (37.9%). The most common anatomic sites involved were the carotid body (33.7%), intracranial regions (29.0%), or cranial nerves (25.5%). Carotid body tumors were exclusively locally invasive, whereas intracranial and cranial nerve HNP were overwhelmingly benign or borderline (94% and 91%, respectively). One-fourth of patients underwent pathologic analysis of regional lymph nodes, of which the majority were positive for metastasis (80.6%). Metastasis to distant organs was twice as common in patients with locally invasive tumors vs benign (15% vs 7.1). For benign disease, surgery with radiotherapy (adjusted hazard ratio [aHR], 40.45; P = .006) and active surveillance (aHR, 24.23; P = .008) were associated with worse survival when compared with surgery alone. For locally invasive tumors, greater age (aHR, 1.07; P < .0001) and positive surgical margins (aHR, 4.13; P = .010) were predictors of worse survival, while combined surgery and radiotherapy were predictors of improved survival vs surgery alone (aHR, 0.31; P = .027). Conclusion: While criteria for tumor behavior could not be defined, our results suggest that such a classification system could be used to enhance HNP risk stratification and guide clinical management decisions.